More perfect than the moon - MacLachlan, Patricia (Joanna Cotler Books, 2004)
Eight-year-old Cassie Witting is upset when she finds out that her mother, Sarah, is expecting a baby, but writing in the journal that belonged to her brother Caleb helps her sort out her feelings and understand that Sarah will always love her.